Behavioral Features of Negative and Malevolent Creativity in Adolescents - Bochkova M.N.; Meshkova N.V. (Психолого-педагогические исследования)
We present the results of research of relationship of antisocial creativity, negative and prosocial creativity in social interaction and their behavioral predictors. The sample consisted of 97 students in grades 9–10 (71 of them boys). We used the questionnaires "The malevolent creativity behavior scale" (adapted by N.Meshkova et al.), Bass-Perry, Machiavellianism, NEO-FFI, "Portrait value questionnaire of Schwartz – revised PVQ-R, Emotional intelligence and social situations to identify prosocial and negative creativity in social interaction. Hypotheses about a) the relationship of malevolent creativity and low self-control («Conscientiousness»); b) emotional intelligence, Machiavellianism, the features of "Agreeableness", aggression and behavioral characteristics of malevolent creativity; c) the negative relationship of emotional intelligence with fluency of harmful decisions in prosocial situation; d) the relationship between fluency in prosocial situation and situation of lies, have been confirmed. The psychological profile of malevolent and negative creativity are described. The directions of further research are proposed.